The Influence of Organizational Climate and Work Environment on Employee Performance with Work Quality as an Intervening Variable at the Belawan Harbormaster and Main Port Authority Office - Henry Dunan; Mesra B; Hernawaty (CV. Doki Course and Training, 2026)
This study aims to analyze the influence of Organizational Climate and Work Environment on Employee Performance, with Work Quality as an intervening variable, at the Harbormaster and Main Port Authority Office in Belawan. The study was conducted in June 2025 for three months. The study location was at the Harbormaster and Main Port Authority Office in Belawan, Jalan Deli Medan, Belawan, Postal Code 20411. The population in this study was 244 employees, and a sample of 151 respondents was determined using the Slovin formula with a 5% margin of error. The sampling technique was proportional to the number of employees in each department. The type of data used was primary data obtained directly from respondents through a questionnaire. The results showed that Organizational Climate and Work Environment had a positive and significant effect on Employee Performance, both directly and indirectly through Work Quality as an intervening variable. Work Quality also had a positive and significant effect on Employee Performance. Thus, it can be concluded that Work Quality plays a mediating role in the relationship between Organizational Climate and Work Environment on Employee Performance. This research implies that improving employee performance can be achieved by strengthening the organizational climate, work environment, and the quality of employee work output.